2021
DOI: 10.1371/journal.pone.0246581
|View full text |Cite|
|
Sign up to set email alerts
|

Blood biomarker discovery for autism spectrum disorder: A proteomic analysis

Abstract: Autism spectrum disorder (ASD) is a neurodevelopmental disorder characterized by deficits in social communication and social interaction and restricted, repetitive patterns of behavior, interests, or activities. Given the lack of specific pharmacological therapy for ASD and the clinical heterogeneity of the disorder, current biomarker research efforts are geared mainly toward identifying markers for determining ASD risk or for assisting with a diagnosis. A wide range of putative biological markers for ASD is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 56 publications
2
47
0
1
Order By: Relevance
“…Pathway analysis using proteomics/transcriptomics data has also pointed to synaptic processes with significant alterations in glutamate (NMDA) receptor signaling identified in various brain regions. In addition, pathways involved in redox mechanisms and inflammatory processes were in the focus ( Voineagu et al, 2011 ; Feng et al, 2017 ; Gandal et al, 2018 ; Schwede et al, 2018 ; Abraham et al, 2019a ; Gordon et al, 2021 ; Hewitson et al, 2021 ). However, there is a lack of overlap between the genes/proteins identified due to the heterogeneity of ASD and different cohorts of varying ages and severity of symptoms used in human proteomic/transcriptomics studies ( Wetie et al, 2015b ; Cortelazzo et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pathway analysis using proteomics/transcriptomics data has also pointed to synaptic processes with significant alterations in glutamate (NMDA) receptor signaling identified in various brain regions. In addition, pathways involved in redox mechanisms and inflammatory processes were in the focus ( Voineagu et al, 2011 ; Feng et al, 2017 ; Gandal et al, 2018 ; Schwede et al, 2018 ; Abraham et al, 2019a ; Gordon et al, 2021 ; Hewitson et al, 2021 ). However, there is a lack of overlap between the genes/proteins identified due to the heterogeneity of ASD and different cohorts of varying ages and severity of symptoms used in human proteomic/transcriptomics studies ( Wetie et al, 2015b ; Cortelazzo et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Suvarna et al (2021) identified protein classifiers of patients with non-severe and severe COVID-19, by using SVMs models (Suvarna et al, 2021). Hewitson et al (2021) used Random Forest and logistic regression models to classify proteins in blood as potential biomarkers in autism spectrum disorder (Hewitson et al, 2021).…”
Section: Artificial Intelligence-based Methodsmentioning
confidence: 99%
“…Overall, data were collated from 19 studies and meta-analyses from ASD cohorts published between 2017 and 2021 ( Table 1 ). The publications included six proteomic datasets [ 11 , 14 , 15 , 16 , 17 , 18 ], eight transcriptomic studies [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ], and five DNAm screens [ 26 , 27 , 28 , 29 , 30 ]. The data collated from each study were the published list of genes or proteins found to be significantly associated with ASD after data quality control, normalisation, processing, statistical analyses and peer review ( Supplementary Table S1 ).…”
Section: Methodsmentioning
confidence: 99%